The Oppressed Anthropology of Dalits Identity: Perspective of Evolution and Modern Nepali society - Rai, Bishnu (Baneshwor Campus Journal of Academia, 2023)
When a person is insulted in the society by tagging one as untouchable, he neither writes news nor agitates that any person has been insulted. Even if he does, he tries to show off by blaming him. So I've tried to raise some issues. In our society, the Dalit caste is viewed with a low and untouchable perversion; it is a rude, adulterous culture. There are also such societies that take it as their tradition and consider it their ethnic ego. Unless we can fight against it, accepting the rule of an alleged class remains the only option. This is not an insult to anyone; it is an anthropological study of how Dalits became and why they are suffering. We want to end this perversion as soon as possible. Inter-caste marriage is in fact a legal trap for Dalits. If the girl or boy you like marries for interracial love, the girl's side will bring the girl back. Chandra Kami of Sarke village in Humla has recently been accused of raping a boy on the side of a girl belonging to a big caste. Similarly, Harikesar Sarki, 10, of Dang Ghorahi Municipality, had a love marriage with a 17-year-old girl from Bohora Thar. He also spent a long time in jail after three months, alleging that the girl's side had committed adultery. But the girl was released from jail after being told that we had a love marriage. But the girl forcibly took the girl away, threatening that the sky and the earth could not be reconciled. Many such incidents have been unfair to Dalits. No democratic, revolutionary leader speaks in this regard. 56-year-old Savitra Kamini of Bajura district recently got citizenship under her old name. Being written in the citizenship certificate as a bitch did not suffer humiliation in the society. Sons and daughters were not even allowed to go to school because they insulted them {August 7, 2079, Kantipur}. It seems necessary to be aware of the situation where this kind of Hindu oppression can lead to violent activities in the society.This is a very popular song sung about the humiliation suffered by the Dalit caste in so-called Hindu upper class society. The singer of this song is Chhewang Lama. I find this song relevant in this research article. This song has raised a big question not only about the plight of Dalits but also about the rituals of Hindu society and our civilize modernity.